High tide: a systematic search for ellipsoidal variables in ASAS-SN. Issue 1 (24th July 2021) - Rowan, D M; Stanek, K Z; Jayasinghe, T; Kochanek, C S; Thompson, Todd A; Shappee, B J; Holoien, T W -S; Prieto, J L
ABSTRACT: The majority of non-merging stellar mass black holes are discovered by observing high energy emission from accretion processes. Here, we pursue the large, but still mostly unstudied population of non-interacting black holes and neutron stars by searching for the tidally induced ellipsoidal variability of their stellar companions. We start from a sample of about 200 000 rotational variables, semiregular variables, and eclipsing binary stars from the All-Sky Automated Survey for Supernovae. We use a χ 2 ratio test followed by visual inspection to identify 369 candidates for ellipsoidal variability. We also discuss how to combine the amplitude of the variability with mass and radius estimates for observed stars to calculate a minimum companion mass, identifying the most promising candidates for high mass companions.